ANALISIS HUBUNGAN KULTUR DAN STRUKTUR ORGANISASI TERHADAP KEEFEKTIFAN PENGANGGARAN PARTISIPATIF - Evi Grediani (Akademi Akuntansi YKPN Yogyakarta, 2012)
This research is intended to evaluate as to whether organization culture and organization structure affect the participative budgeting as well as the manager performance. Fifty six sample selected randomly in this research. The sample are managers or supervisors in the Public Accountant Firms in Indonesia. Hypotheses are tested using multiple regression. The two conclusion of the research are: firstly, the relation between participative budgeting and the organization culture is negative and significant, it means that the job-oriented organization culture affects the relationship between the effectiveness of participative budgeting to the performance of manager and secondly, the relation between the effectiveness of participative budgeting and organization structure is negative and significant, it means that a centralized organization structure affects the effectiveness of participative budgeting and the performance of manager.Keywords: the organization culture, the organization structure, the participative budgeting, the performance of manager.